(untitled) (Revista de História da UEG (REVHIST), 2022)
This article aims to analyze the theses from the Green Blouses, published in the newspaper A Offensiva (1934-1938), referring to the month of September 1936, which had the purpose of educating and training women within the integralist ideology. The Ação Integralista Brasileira (1932-1938) was a Brazilian fascist movement, coordinated by its boss, the novelist Plínio Salgado. As the press is the most recurrent way of disseminating integralist ideals, we look at the weekly newspaper A Offensiva, with its national reach, to understand the importance of women for the integralist movement and the social roles assigned to them based on their biological sex. For this analysis, we use gender and political affectivities as the category of analysis, which provide an analytical look at how the moving messages were directed and structured in the journalistic discourse of A Offensiva, incorporating motherhood as the primary source of women’s participation in the movement. Key-Words: Integralism. Woman. Motherhood. Gender.